Determination of Pollutant Index (PI) for Assessing the Quality of Groundwater in the Area of Sidoarjo Mud (LUSI) Sidoarjo, East Java, Indonesia; Jurnal Sumberdaya Alam dan Lingkungan; Vol. 10, iss. 2 - Adiyaksa I. P. Ilham Putra (2023, 2023)
Title screen